Peran Ekonomi Pendidikan Dalam Mendorong Kewirausahaan Di Kalangan Pelajar - Rima Septia Maulani; Eka Oktapiani; Neni Rosmiati (CV. Akira Java Bulu, 2025)
Abstract is in English covering the central issues of the study, the objectives, the methods/approaches and the results of the study. Abstract consists of one paragraph, not to exceed 200 words. (Times New Roman – 11 – single space – italic). Economics education plays a crucial role in shaping students' entrepreneurial mindsets, skills, and character. This article discusses how the application of economic concepts in education can foster entrepreneurial interest and skills among students. This research utilizes a literature review method from various relevant sources on the relationship between education, economics, and entrepreneurship. The analysis shows that integrating entrepreneurship materials into the curriculum, business soft skills training, and school ecosystem support can foster student creativity, innovation, and independence. An understanding of economic values and resource management is also crucial for creating business opportunities from an early age. Thus, economics education serves not only as a medium for imparting knowledge but also as a means of empowering students to contribute to economic development through entrepreneurship